(untitled) (Botanica Orientalis: Journal of Plant Science, 2025)
Sowa Rigpa, also known as Tibetan or Amchi medicine, is one of the traditional systems of medicine practiced across an extensive region of South, Central, and East Asia. Sowa Rigpa pharmacopeia is based on plants, animals, minerals, and other natural substances. Among the plant-based ingredients, a bi sa is derived from different Himalayan species belonging to the family Liliaceae. The most commonly used plant species as a source of a bi sa in Nepal is Fritillaria cirrhosa. However, F. cirrhosa is highly threatened throughout the Himalayas mainly due to the overharvesting of its underground bulbs to meet the increasing global demand for these bulbs in the herbal market. Conservation of remaining F. cirrhosa populations in the wild is immediately needed, which requires measures such as the prevention of illegal harvesting, protection of natural habitats, promotion of sustainable harvesting practices, and implementation of enrichment planting and ex-situ conservation strategies. The current review provides an overview of the taxonomy, morphological variability, ecology, and ethnomedicinal importance of F. cirrhosa; and highlights its socio-cultural, economic, and conservation importance.